Evaluasi Potensi Emisi Gas Rumah Kaca Di Peternakan Sapi Potong Di Kecamatan Paseh Kabupaten Sumedang - Sukmono, Agung; Imanudin, Oki; Widianingrum, Dini (Tropical Livestock Science Journal, 2024)
The purpose of this study was to inventory methane gas emissions from beef cattle farms in Paseh District, Sumedang Regency. The method in this study is a survey method. Data analysis used in this study is descriptive with primary data derived from interviews, direct physical observations in the field and questionnaire data. Determination of the number of questionnaire samples was purposive. The results showed that CH4 gas emissions from enteric fermentation of beef cattle in Paseh District with a population of 86 beef cattle contributed 0.00291 Gg CH4/year or equivalent to 2,91 tons CH4/year. The highest methane emissions from enteric fermentation were produced by the Mayang Tanjung Mekar group with a population of 35 cattle producing methane emissions of 0.00118 Gg CH4/year, while the lowest were produced by the Kondang Jaya and Salak Mukti groups with a population of 8 cattle producing methane emissions of 0.00027 Gg CH4/year. The conclusion of this study is that the beef cattle farming sector from enteric fermentation in Paseh District contributes to producing methane gas emissions, to minimize the impact of these emissions, farmers can carry out engineering or pay attention to good livestock feed management.